Antiparasitic defenses in hosts of South American cowbirds - Reboreda, Juan Carlos (2013)
The cowbirds (Molothrus, Icteridae) are a monophyletic group that includes five extant brood-parasitic species. The Screaming (M. rufoaxillaris), Giant (M. oryzivorus) and Shiny (M. bonariensis) cowbirds range mostly in South America. Screaming and Shiny cowbirds are the ancestral and most recent species of the clade, respectively, therefore, differing in how long they have coevolved with their hosts. We present new experimental data on egg-rejection in a host of the Shiny Cowbird, the House Wren (Troglodytes aedon), review different lines of antiparasitic defenses in hosts of Screaming, Giant and Shiny cowbirds and assess whether hosts of different parasites differ in the type and extent of defenses. Hosts of all three parasites ejected non-mimetic eggs. Most hosts of Giant and Shiny cowbirds were grasp ejectors, whereas the main host of the Screaming Cowbird (the Baywing, Agelaioides badius) ejected parasitic eggs using its feet. Hosts smaller than Shiny Cowbirds neither ejected cowbird eggs nor deserted nests following parasitism. Some hosts also reacted more aggressively towards the parasite. The main host of Screaming Cowbird discriminated against non-mimetic chicks. Our results show that most hosts, regardless of the presumed evolutionary time of interaction with the parasite, have evolved some type of antiparasitic defense.